Mature embryo-derived wheat transformation with major stress-modulated antioxidant target gene - Galovic, Vladislava; Rausch, Thomas; Grsic-Rausch, Slobodanka (Archives of biological sciences, 2010)
The mature embryos of fourteen elite winter wheat cultivars have been transformed by a biolistic approach. The gene coding for γ-glutamylcysteine synthetase (EC 6.3.2.2) was used as a transgene in order to obtain stable transformants resistant to drought stress. A binary vector, pBinarUTRECS, was used. The gene was under the control of the CaMV35S promoter region. GUS::GFP gene fusion was used as a reporter system and nptII served as a selectable marker gene. A high regeneration capacity of callus tissue under the selective pressure and successful GUS assay of transformed tissue were an indication of successful insertion of a transgene into mature embryo derived wheat tissue. .
Gesehen am 25.07.2023